In- vitro antioxidant and In vivo Anti-inflammatory Potentials of Marantochloa Leucantha (Marantaceae) Extracts and Fractions (Dhaka University Journal of Pharmaceutical Sciences, 2019)
This study evaluated the antioxidant and anti-inflammatory properties of Marantochloa leucantha (Marantaceae). The in vitro antioxidant activity of the extracts and solvent fractions was evaluated by 1,1-diphenyl- 2-picrylhydrazyl (DPPH) radical scavenging and ferric reducing antioxidant potential (FRAP) assay models and in vivo anti-inflammatory activity by the rat paw edema model. The phytochemical screening indicated the presence of tannins, terpenoids, steroids, flavonoids, reducing sugar and phenolics. The antioxidant assay showed that all the extracts exhibited high antioxidant activity comparable with ascorbic and gallic acid controls. In DPPH model, a 250 μg/ml EtOAc fraction of the leaves showed antioxidant activity of 93.9 ± 1.7 % (EC50 0.82 μg/ml) and a 1000 μg/ml of same stem fraction produced 91.9 ± 0.3 % activity (EC50 1.38 μg/ml). In the FRAP model, EtOAc fraction exhibited 31.1±0.7 and 92.0 ± 2.2 μM Fe2+/g of dried leaves and stem, respectively at 1000 μg/ml FeSO4 equivalent. The anti-inflammatory potential of the plant showed that the crude stem extract and fractions at 200 - 600 mg/kg exhibited significant (p < 0.01) dose-related inhibition of paw edema in rats. A 200 mg/kg EtOAc fraction showed 18.8 % inhibition compared to 31 % observed in diclofenac-treated rats in 2 h post albumin challenge. These findings validated the folkloric use of this plant in the treatment of diseases associated to the oxidative stress and could further provide promising lead compounds with potent antioxidant and anti-inflammatory activitiesDhaka Univ. J. Pharm. Sci. 18(2): 233-240, 2019 (December)